Streets, Ballots, and Bullets: Kurdish Engagement and Activism - Sharifi, Massoud (PARTECIPAZIONE E CONFLITTO, 2025)
This article analyzes profiles, trajectories, motivations, and subjectivity of individuals opting to join pro-Kurdish organizations, associations, or political parties in Turkey. Departing from organizational-centric models, it applies an analytical approach rooted in social movement theories, emphasizing agency-centered perspectives to analyze pro-Kurdish activism. The research encompasses seventeen organizations, spanning locations in Turkey, Iraqi Kurdistan, and France, drawing on 77 semi-structured interviews, including 11 with former militants and guerrillas. The article examines the demographic characteristics of Kurdish activists and identifies three groups: associative, office, and professional activists. Through a comparison of dimensions such as degree of investment, ideological commitment, autonomy of action, and objectives, the study aims to provide nuanced understanding of these activism forms. Furthermore, the research delves into the biographical narratives of Kurdish activists, tracing motivations guiding their alignment with associations, political parties, or armed groups. Finally, the actor-event dialectic is employed to elucidate the rhythm of engagement, analyzing events at different life stages as accelerators, conjunctions, or sequences influencing participation. The actor-centric perspective enhances understanding of motivations and dynamics influencing engagement in pro-Kurdish activism in Turkey, and sheds light on an emerging trend within the Kurdish movement, positioning itself as the confluence of various social, cultural, and political conflicts.